Saved by trust: When extensive supply chain integration becomes detrimental - Hamdi, Ahmed; Saikouk, Tarik; Bahli, Bouchaib; Anand, Amitabh (Management international / International Management / Gestiòn Internacional, 2023)
This paper refines existing literature on supply chain integration (SCI) by exploring its possible adverse effects on higher levels of SCI on firm performance. Furthermore, we explain how trust offsets the negative effects of increased integration. Based on data gathered from 152 firms in the United States, our research reveals two important results: (1) an inverted U-shaped relationship exists between supplier integration and firm performance, (2) the levels of trust attenuate the effects of increased integration on firm performance. Finally, using the relational view and transaction costs theory, we discuss the theoretical and managerial implications of our research results.